Problem Based Learning and Guided Inquiry Learning Model on Critical Thinking Ability - Rejeki, Suprapti; Riyadi, Riyadi; Siswanto, Siswanto (Universitas Ahmad Dahlan, 2021)
This research aims to determine the distinction in students' critical thinking abilities who were taught by using the problem-based learning, guided inquiry learning, and conventional learning models. The population is all grade VIII students of public junior high schools in Bantul district in the 2019/2020 academic year. This study used stratified cluster random sampling to select 3 classes in each school. The pre-requisite test used was the balance test, normality test, and homogeneity test. The data collection technique used was a critical thinking ability test. The analysis technique of this research was two-way ANOVA with different cells. The results showed that the problem-based learning model had a significant positive effect on the critical thinking abilities compared to conventional learning. Meanwhile, there is no significant difference between students taught by problem-based learning and by guided inquiry learning, and between the guided inquiry learning and conventional learning, either.